Tyrosine Kinase Inhibitors (TKIs) in Lung Cancer Treatment: A Comprehensive Analysis - Murugesan, Sivakumar; Murugesan, Jayakumar; Palaniappan, Seedevi; Palaniappan, Sivasankar; Murugan, Tamilselvi; Siddiqui, Shahid S.; Loganathan, Sivakumar (Current Cancer Drug Targets, 2021)
Lung cancer is the leading type of cancer worldwide today. Kinases play a crucial role in mediating the signaling pathways, and it directs to control several necessary cellular processes. Conversely, the deregulation of tyrosine kinases leads to oncogenic conversion, uncontrolled cell proliferation and tumorigenesis. Tyrosine kinases are largely deregulated in lung cancer and specifically in non-small cell lung cancer (NSCLC). Therefore, the inhibition of pathogenic kinases is a breakthrough development in cancer research, treatment and care, which clinically improve the quality of life. In the last decades, various single or combination inhibitors are approved by U.S Food and Drug Administration (FDA) and commercially available in clinics, and currently, several preclinical studies are ongoing and examining the kinase inhibitors. However, many gaps remain in understanding the mechanisms of kinase inhibitors and their selectivity. In this analysis, we focus on a class of receptor and non-receptor tyrosine kinase inhibitors and their novel role in lung cancer.
Keywords: FDA approved drugs